Can leisure and entertainment lifestyle promote health among older people living alone in China?—A simultaneous equation approach - Qin, Yinghua; Liu, Jingjing; Wang, Rizhen; Qi, Xinye; Jiang, Shengchao; Li, Jiacheng; Guo, Pengfei; Wu, Qunhong (Frontiers in Public Health, 2022)
Objectives With the surging number of older people living alone, their lifestyles and health status have aroused increasing concern. This study aims to investigate whether a leisure and entertainment lifestyle (LEL) can improve the multidimensional health among older people living alone and try to identify the latent mechanisms among them. Method For this purpose, we extracted data from the Chinese General Social Survey (CGSS) and established a simultaneous equations model, comprising ordinary least square regression (OLS), two-stage least squares (2SLS), and the mediating effect model. Results Older people living alone in China reported relatively better mental health status (3.64 ± 1.07), followed by physical health (3.41 ± 1.26) and social health (2.75 ± 1.18). In the OLS model, LEL significantly improved the social health of older people living alone (β = 0.054, P < 0.01), followed by physical health (β = 0.042, P < 0.01) and mental health (β = 0.027, P < 0.01). After endogenous tests from 2SLS model and robustness tests, we found that more active LEL was associated with higher levels of physical health and mental health. However, LEL had no significant effect on the improvement of the social health of the older people living alone. Using the mediation analysis, exercise efficacy partially mediated the relationship of LEL with physical health and mental health, and the ratios were 19.75 and 24.85%, respectively. Similarly, positive life attitudes partially mediated the relationship between LEL and physical health, and LEL and mental health, with ratios of 10.65 and 26.83%, respectively. Conclusion Our findings suggested that LEL is significantly associated with better physical and mental health for older people living alone in China, and the association is mediated by exercise efficacy and positive attitudes toward life. Promoting more leisure and recreational activities, upgrading exercise efficacy, and encouraging positive life attitudes are necessary health promotion measures in active aging policies for the wellbeing of older people living alone.